2020
DOI: 10.7717/peerj.8781
|View full text |Cite
|
Sign up to set email alerts
|

Agility-based exercise training compared to traditional strength and balance training in older adults: a pilot randomized trial

Abstract: Background In addition to generally high levels of physical activity, multi-component exercise training is recommended for the maintenance of health and fitness in older adults, including the prevention of falls and frailty. This training often encompasses serial sequencing of balance, strength, endurance and other types of exercise. Exercise training featuring integrative training of these components (i.e. agility training) has been proposed, as it more likely reflects real life challenges like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 41 publications
3
29
1
Order By: Relevance
“…Earlier data has shown that yoga, Pilates, dance, Tai Chi and stretching can improve the flexibility of the elderly (Saravanakumar et al, 2018). On the contrary, multi-component training of 50 min, three times a week for eight weeks did not affect static balance (Lichtenstein et al, 2020). Balance training is considered task specific (Kümmel et al, 2016) and programs to improve balance suggest 90-120 min of balance training per week for 11-12 weeks (Lesinski et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier data has shown that yoga, Pilates, dance, Tai Chi and stretching can improve the flexibility of the elderly (Saravanakumar et al, 2018). On the contrary, multi-component training of 50 min, three times a week for eight weeks did not affect static balance (Lichtenstein et al, 2020). Balance training is considered task specific (Kümmel et al, 2016) and programs to improve balance suggest 90-120 min of balance training per week for 11-12 weeks (Lesinski et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there were very few studies comparing single training and combined training. Most of these combination exercises training had a greater effect on physical performance in older adults than single exercise training (Fatouros et al, 2002;Karinkanta et al, 2007;Cancela Carral and Ayán Pérez, 2008;Carvalho et al, 2010;Sousa et al, 2013aSousa et al, ,b, 2017Lee et al, 2015;Haripriya et al, 2018;Timmons et al, 2018;Lichtenstein et al, 2020). This was because the combination exercises involve more elements that engage in physical performance, so they produce more comprehensive and effective results than single exercises (U.S. Department of Health and Human Services, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive multimodal agility training concepts bring the advantage of reproducing real-life conditions and therefor offer more opportunity for transfer; however, this must be investigated more. With this in mind, the results of a first pilot-study [53] are promising and the evaluation of an innovative agility training approach within an RCT study [54] could provide further insights about the effects of agility training in older adults. Thus, the present meta-analysis highlights the importance of MAT for older adults and provides important insights for future training conceptualization.…”
Section: Discussionmentioning
confidence: 99%
“…However, the perceptual aspects of agility training and the characteristics of an original definition by Sheppard and Young [52]: "a rapid whole-body movement with change of velocity or direction in response to a stimulus", comprising a perceptual decision-making process and its outcome, a change of direction or velocity task is often missing in recent studies. A recently published pilot study [53] specifically included agility-based exercises being based upon the agility approach by Donath et al [12]. In addition, Morat et al [54] published the protocol of their planned RCT evaluating agility training for older adults.…”
Section: Effects On Mobilitymentioning
confidence: 99%